ELECTRICAL TRANSITIONS IN CORRELATION STATES OF DEFORMATIONAL ATOMIC NUCLEI - Kabulov, A.B. (Recent Contributions to Physics, 2008)
Probabilities of E2-trasitions are obtained in the frame of U(6) U(4) symmetry in correlation states of deformational nuclei. Calculations are maked in symmetry and second-order perturbation.